2009
DOI: 10.2353/ajpath.2009.080924
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Cell Expression of Caveolin-1 Predicts Outcome in Breast Cancer

Abstract: Caveolin-1 has been linked to tumor progression and clinical outcome in breast cancer, but a clear resolution of its role as a prognostic marker is lacking. We assessed caveolin-1 levels in normal breast tissue and two breast cancer cohorts for which outcome data were available. We found that caveolin-1 was not expressed in normal breast luminal epithelium but was present in the epithelial compartment of some tumors. We found no association between caveolin-1 expression in the epithelial compartment and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
169
5
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(187 citation statements)
references
References 36 publications
12
169
5
1
Order By: Relevance
“…A loss of stromal Cav-1 and an upregulation of stromal MCT4 are markers of oxidative stress associated with poor clinical outcome in breast cancer. [34][35][36][37][38][39][40][41][42] Figure 3A and B shows that fibroblasts overexpressing UCP1, UCP2 and UCP3 all induce the downregulation of Cav-1 expression and increase MCT4 levels, as compared with control cells.…”
Section: Resultsmentioning
confidence: 97%
“…A loss of stromal Cav-1 and an upregulation of stromal MCT4 are markers of oxidative stress associated with poor clinical outcome in breast cancer. [34][35][36][37][38][39][40][41][42] Figure 3A and B shows that fibroblasts overexpressing UCP1, UCP2 and UCP3 all induce the downregulation of Cav-1 expression and increase MCT4 levels, as compared with control cells.…”
Section: Resultsmentioning
confidence: 97%
“…We and others have previously shown that a loss of stromal Cav-1 is associated with early tumor recurrence, metastasis, tamoxifenresistance and poor clinical outcome in human breast cancer patients. [22][23][24][25][26][27][28][29][30] Similarly, Cav-1 knock-down fibroblasts increase tumor growth, up to ~four-fold, when they are co-injected with increase in glucose uptake, as we observe in stromal fibroblasts that are co-cultured with cancer cells. Figure 12 shows that we successfully created stable Cav-1 knock-down fibroblasts, using an siRNA-based approach.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 91%
“…[22][23][24][25][26][27] Thus, this type of metabolism (aerobic glycolysis and autophagy in the tumor stroma) is characteristic of a lethal tumor micro-environment, as it fuels anabolic growth in cancer cells, via the production of high-energy nutrients (such as lactate, ketones and glutamine) and other chemical building blocks (fatty acids, nucleotides, amino acids). 4,11,40 Interestingly, we show here that the upstream tumor-initiating event appears to be the secretion of hydrogen peroxide by MCF7 cancer cells under co-culture conditions.…”
Section: -610mentioning
confidence: 99%
See 1 more Smart Citation
“…24,26 This has important clinical implications, as we and others have previously shown that a loss of stromal Cav-1 in human breast patients is a strong predictor of early tumor recurrence, metastasis, tamoxifen resistance and overall poor clinical outcome. [29][30][31][32][33][34][35][36][37][38][39] Similarly, elevated MCT4 in cancer-associated fibroblasts is predictive of a poor clinical outcome in breast cancer patients, and strictly correlates with a loss of Cav-1. 40 Thus, our current results with co-culture directly mirror what occurs in a specific subset of high-risk human breast cancers in patients in vivo.…”
Section: Discussionmentioning
confidence: 99%